Ethnomedicinal, phytochemical and pharmacological properties of Piper longum (Linn) - Gani, Hakim Md Osman; Hoq, Md Obydul; Tamanna, Tahmina (Asian Journal of Medical and Biological Research, 2019)
Herbs orchestrate resurgence and vegetal awakening is supervened everywhere in the world. Medicinal plants always played an important role in the health development of mankind. Piper longum provides us new lead molecules for the development of drugs against various pharmacological targets. Plants included in this family are annual and persistent herbs or shrubs, indigenous to northern moderate stretch of the world. Piper longum is well known for its medicinal and pharmaceutical importance. In this review studies we will want to explore the various pharmacological properties of Piper longum in Unani system of medicine. Evidence suggests that various listed of Unani Medicine formulated with the Piper longum among these few are tablet, capsule, syrup and semi-solid etc. The primary constituents isolated from various parts of P. longum are piperine, piperlongumine, sylvatin, sesamin, diaeudesmin piperlonguminine, pipermonaline, and piperundecalidine. It is most commonly used to treat chronic bronchitis, asthma, constipation, gonorrhea, paralysis of the tongue, diarrhea, cholera, chronic malaria, viral hepatitis, respiratory infections, stomachache, bronchitis, diseases of the spleen, cough, and tumors. This study provides detailed information about the P. longum fruit, including phytochemistry, pharmacological profile and safety profile. Asian J. Med. Biol. Res. March 2019, 5(1): 1-7